CHARACTERISTICS OF DISABLED CHILDREN BORN WITH CONGENITAL ANOMALYS IN FERGANA REGION - PhD Kasimova D. A.; Fayzullayeva X. A. (Web of Journals Publishing, 2025)
Congenital anomalies are structural or functional defects present at birth. Such conditions can lead to physical or mental disabilities in children. The impact of congenital anomalies varies greatly depending on their type and the general health of the child. This article examines the specific characteristics of children with disabilities born with congenital anomalies, their difficulties and methods of supporting their development, and the current state of examination and analysis of children with disabilities in the Fergana region.
Keywords: Сongenital anomalies, hereditary factors, infection, children with disabilities, polyorgan, polymorphic, pathology, hyperactivity, autism, skeletal, craniofacial, neurological, septal defects, deformation, Down syndrome, cognitive, orthopedic supports, stigmatization, inclusive education, individual assistance, integration, optic nerve atrophy, musculoskeletal diseases, connective tissue, injury, malignant neoplasms, poisoning.